2010
DOI: 10.1158/1940-6207.capr-09-0110
|View full text |Cite
|
Sign up to set email alerts
|

Profiling Lipoxygenase Metabolism in Specific Steps of Colorectal Tumorigenesis

Abstract: Lipoxygenases (LOX) are key enzymes for the oxidative metabolism of polyunsaturated fatty acids into biologically active products. Clinical data on comparative levels of various LOX products in tumorigenesis are lacking. Therefore, we examined the profiles of several LOX products (5-LOX, 12-LOX, 15-LOX-1, and 15-LOX-2) by liquid chromatography/tandem mass spectrometry in the major steps of colorectal tumorigenesis (normal, polyp, and cancer) in a clinical study of 125 subjects (49 with normal colon, 36 with co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
67
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(76 citation statements)
references
References 38 publications
8
67
1
Order By: Relevance
“…Notably, high expression of 5-LOX was also observed in individual cells within the stroma, consistent with inflammatory cell phenotype, though inflammatory markers were not stained for in the same sections. In contrast to the study by Shurequi et al, [91], we observed a modest increase in expression of 12-LOX in many colorectal cancers, though both villous and tubulovillous adenomas expressed levels of 12-LOX similar to normal colon. While our study is only descriptive, it would suggest that 5-LOX expression is an early event in the sequence to colon cancer, with increased expression in adenoma frequent, while 12-LOX expression would appear to be a later event, possibly mediating invasion and metastasis.…”
Section: Lipoxygenase Pathwaycontrasting
confidence: 99%
See 1 more Smart Citation
“…Notably, high expression of 5-LOX was also observed in individual cells within the stroma, consistent with inflammatory cell phenotype, though inflammatory markers were not stained for in the same sections. In contrast to the study by Shurequi et al, [91], we observed a modest increase in expression of 12-LOX in many colorectal cancers, though both villous and tubulovillous adenomas expressed levels of 12-LOX similar to normal colon. While our study is only descriptive, it would suggest that 5-LOX expression is an early event in the sequence to colon cancer, with increased expression in adenoma frequent, while 12-LOX expression would appear to be a later event, possibly mediating invasion and metastasis.…”
Section: Lipoxygenase Pathwaycontrasting
confidence: 99%
“…A recent study by Shureiqi et al, examined 5-LOX, 12-LOX, 15-LOX-1 and 15-LOX-2 in a prospective study of 125 patients [91]. No differences in 12-or 15-HETE or leukotriene B(4) levels were observed between normal, polyp and cancer mucosae; however, the expression of the 15-LOX-1 product, 13(S)-HODE, was lost across this progressive sequence.…”
Section: Lipoxygenase Pathwaymentioning
confidence: 99%
“…Decreased expression of 15-LOX-1 in human CRC is associated with IL-1b upregulation; 15-LOX-1 re-expression in CRC cells inhibits IL-1b [89], which is a major proinflammatory cytokine that contributes to the pathogenesis of human colitis [93]. These results show that 15-LOX-1 may attenuate colitis by downregulating the expression of IL-1b.…”
Section: -Lox-1 and Colorectal Cancermentioning
confidence: 73%
“…These results indicate that 15-LOX-1 can serve as a tumor suppressor gene. Re-expressed 15-LOX-1 in CRC inhibits the expression of IL-6b [89], which is a major pro-inflammatory cytokine that contributes to the pathogenesis of human colitis [90]. STAT3 is activated in tumors from the lung, breast, kidneys, cervix, ovaries, head and neck, and prostate, as well as in pancreatic carcinoma, melanoma, colon carcinoma, gastric carcinoma, hepatocellular carcinoma, multiple myeloma, and chronic lymphocytic leukemia [91].…”
Section: -Lox-1 and Colorectal Cancermentioning
confidence: 99%
“…Findings from this and the current study could be interpreted as suggesting that PGE 2 promotes colonic tumorigenesis at stages later than ACF and adenomas. Of note, a recently published study has showed no significant change in leukotriene B 4 levels during colonic tumorigenesis (33), calling into question whether 5-HETE really is a biomarker for colorectal tumorigenesis. The current study is limited in assessing the role of these pathways in colonic tumorigenesis by its relatively small sample size and single pathological endpoint.…”
mentioning
confidence: 99%